PERAN MASYARAKAT DALAM PENGEMBANGAN WILAYAH - Ulan Aryantini Amir; Hasti Widyasamratri (UNHI Press, 2021)
Indonesia consists of a vast area of ​​land and sea, therefore the utilization of the arrangement needs to be made for the welfare of the community. At this time there are still many people who are indifferent and do not understand the essence of spatial planning. Spatial planning is contained in Law No. 26 of 2007. Regional development is the process of directing the potential of the area to be used comprehensively to realize the welfare of the community. The empowerment process is usually a combination of several mutually supportive factors. Regional development is a form of effort to build and develop regions using a spatial approach by considering socio-cultural, economic, natural, and institutional aspects in the planning framework. Regional development and spatial planning that have been planned by the government depend on the role and participation of the community. In the realization of regional development, the role of the community is very much needed in determining the success of regional development plans. Keywords: spatial planning, community role, regional development, regional growth